Density-constrained TDHF calculation of fusion and fission barriers - Umar, A. S.; Oberacker, V. E.; Maruhn, J. A.; Reinhard, Paul-Gerhard (AIP Conference Proceedings, 2009)
The density-constrained time-dependent Hartree-Fock (DC-TDHF) theory is a Mly microscopic approach for calculating heavy-ion interaction potentials and fusion cross sections below and above the fusion barrier We discuss applications of DC-TDHF method to fusion, the effects of neutron transfer, and potential application to fission barrier calculations. © 2009 American Institute of Physics.
CRIS-Team Scopus Importer:2023-07-24
Keywords: Density constraint; Fission barrier; Fusion barrier; TDHF